The Impact of Occupational Health and Safety Measures on Employee Performance at the South Tongu District Hospital (Global Journal of Medical Research, 2017)
The study is about the impact of OHS measures on employee performance at the South Tongu District Hospital. The aim is to find out the level of employee awareness of the OHS Policy of the Ghana Health Service, determine whether the OHS Policy has been implemented in the organisational setup, identify the kinds of hazards that employees face due to the nature of their work, identify the challenges face in the implementation of OHS measures by management and finally to examine the impact of the OHS measures on employee performance. The study used both stratified and simple random sampling methods to sample 116 employees of the Hospital including 5 management members. Questionnaires were administered and observation was carried out. However, only 88 questionnaires were retrieved and analysed using the SPSS software and results were displayed on tables. The study found out that the level of employee awareness of OHS Policy was 79.5 percent. The measures were seen to have been implemented adequately. Workers faced numerous hazards such as safety hazards, mechanical hazards, biological hazards, ergonomic, physical hazards and psychological hazards. Management was found to be constrained financially in the implementation and maintenance of OHS measures.